Intensive Archeological Survey of the City of Longview 12-inch Diameter Water Line from the Garland Road/Estes Drive Intersection to the Booster Pump Station at the East Texas Regional Airport, Longview, Gregg County, Texas - Ralph, Ronald W. (Archeological Assessments (Firm), 2012)
Report describing an archaelogical survey of an area near Longview, Texas, including a background literature search, an interview with a pertinent landowner, and a pedestrian survey with shovel testing of the entire water line corridor.